Coincidence point and fixed point theorems for rational contractions - OPREA, Anca Maria (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The purpose of this work is to present some coincidence point theorems for singlevalued and multivalued rational contractions. A comparative study of different rational contraction conditions is also presented. Our results extend some recent theorems in the literature. Mathematics Subject Classification (2010): 47H10, 54H25.